2004
DOI: 10.1007/s11236-005-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Immersion tomographic study of the motion of bubbles in a flooded granular bed

Abstract: The microstructure and dynamics of two-phase gasliquid flows in packings and granular beds remain a challenging problem in several fields of advanced engineering, such as chemical technology, the power industry, and petroleum and gas production. The creation of physical and computational models and methods is limited by the unobtainability of visual observations of phase interactions in such flows. Immersion tomography of a gas-liquid medium in a granular bed, a recently developed technique, provides a new mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…These are exemplified in figure 2. In mode 1, small bubbles percolate up through the interstitial spaces in the granular bed presumably in the manner studied experimentally by Roosevelt & Corapcioglu (1998), Brooks et al (1999), Pokusaev et al (2004) and others. In the present case, these bubbles could emerge from a single site on the bed surface (at low flow rates or with large beads) or multiple sites (at high flow rates or with smaller beads).…”
Section: Experimental Observationsmentioning
confidence: 79%
See 2 more Smart Citations
“…These are exemplified in figure 2. In mode 1, small bubbles percolate up through the interstitial spaces in the granular bed presumably in the manner studied experimentally by Roosevelt & Corapcioglu (1998), Brooks et al (1999), Pokusaev et al (2004) and others. In the present case, these bubbles could emerge from a single site on the bed surface (at low flow rates or with large beads) or multiple sites (at high flow rates or with smaller beads).…”
Section: Experimental Observationsmentioning
confidence: 79%
“…Consequently, the emerging bubble size is determined by the balance of surface tension and buoyancy forces as previously described in the porous media literature (see e.g. Pokusaev et al 2004). This can be demonstrated in two simple but equivalent ways by considering a large bubble of diameter, D, in a packed bed of grains with diameter, d, filled otherwise with liquid of density, ρ, and surface tension, S.…”
Section: Theoretical Analyses Of the Bubble Sizementioning
confidence: 93%
See 1 more Smart Citation
“…gives a minimum detectable bubble radius of 0.6 mm. Bubbles closer together than the pixel resolution of the image (780 m) will not be individually identified, therefore 'swarms' or 'flocks' of small bubbles travelling together in, for example, bubble trains (Pokusaev et al, 2004b), will be identified as a single long bubble in the present work. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous examples of the use of optical techniques for tracking of gas bubbles; for example, Benkrid et al (2002), Pokusaev et al (2004 a,b), Bordas et al (2006), Mena et al (2008), Jo & Revankar (2009. In particular, Pokusaev et al (2004b) released small numbers of bubbles of 0.4-2 mm in diameter into the centre of a packed bed of 3 mm diameter glass spheres, with n-decane as the liquid phase. It was found that the rise velocity of the bubbles increases significantly with bubble size.…”
Section: Introductionmentioning
confidence: 99%